Factors Influencing Visit Intention in Medical Tourism in Indonesia - Ferdinand Sukher; Dewi Sri Surya Wuisan (Eduvest - Journal of Universal Studies, 2025)
Public health awareness has grown alongside technological progress, as broader access to information now enables individuals to easily obtain health knowledge from diverse sources. This study aims to examine how attitude, subjective norms, perceived behavioral control, destination image, electronic word of mouth, and perceived risk influence medical tourism visit intention. This research seeks to provide a more comprehensive understanding of the factors influencing individuals’ intention to engage in medical tourism abroad. The study employed the PLS-SEM method. Data from 304 respondents were collected cross-sectionally using an online questionnaire. The results of this study confirm the hypotheses regarding the relationships between attitude, subjective norms, perceived behavioral control, electronic word of mouth, and destination image with visit intention. All five variables individually have a significant positive correlation with visit intention. The findings of this study support the improvement of attitude and subjective norms as priorities in developing Indonesia’s medical tourism sector.